A framework for developing Pervasive Awareness Systems in smart environments. (23rd May 2012) - Goumopoulos, Christos; Kameas, Achilles D.; Berg, Erik
Pervasive Awareness Systems (PASs) collect awareness information from sensors and devices in smart environments and can present it to remote users by using various awareness objects. In this paper, we present a pervasive awareness management framework for supporting the conception, design and realisation of applications that foster social connectedness between communities. The framework consists of: 1) an awareness model that considers user disturbance and privacy; 2) a service–oriented platform that provides core awareness services; 3) assorted tools that support communities to create, adapt and appropriate such applications. A PAS prototype is presented along with a usability evaluation of the tools.